Ultralong photoluminescence lifetime enables efficient tin halide perovskite solar cells - Miao Zhang; Peng Wang; Huanhuan Yao; Cheng Wu; Mingyu Yin; Hongju Qiu; Jie Luo; Jialin Du; Yong Hua; Feng Hao (Next Materials, 2025)
Lewis base additives typically undergo interactions with SnI2 to achieve effective defect passivation in lead-free perovskite films. In this work, the thiophene ring in 2-thiophenethylammonium chloride (TEACl) has coordination interactions with Sn2+ and the -NH3+ therein forms hydrogen bonds with I-. This facilitates the deposition of homogeneous and dense films with fewer defects during crystallization process. Otherwise, 2-pyridinethylammonium chloride (AEPCl) gives poorly perovskite films with high defect density because of the overly strong interaction with SnI2. As a result, the average photoluminescence life time of TEACl-passivated perovskite film was substantially increased to 22.04 ns, compared with the control film (5.15 ns) and the AEPCl-passivated film (3.55 ns). Ultimately, the target solar cell with TEACl passivation presented a power conversion efficiency of 13.24% and excellent shelf-stand stability with a 90% retaining of initial efficiency after 2000 h of aging in N2 atmosphere. This work sheds new light on the structural tailoring of Lewis base passivators for efficient defect passivation in lead-free tin halide perovskites.